Pharmacogenetic testing revisited: 5′nuclease real-time polymerase chain reaction test panels for genotyping CYP2D6 and CYP2C19 - Larsen JB; Rasmussen JB (Dove Medical Press, 2017)
Jens Borggaard Larsen, Jan Borg Rasmussen Laboratory Unit, Danish Epilepsy Centre, Filadelfia, Dianalund, Denmark Abstract: Due to their involvement in the metabolization of commonly prescribed psychopharmaceutical drugs, the cytochrome oxidase genes CYP2D6 and CYP2C19 are extensive targets for pharmacogenetic testing. The existence of common allelic variants allows the prediction of a metabolic phenotype based on a genotype result, hereby supplying a clinical tool for optimizing prescription and minimizing adverse effects. In this study, we present the development of two 5′ nuclease real-time polymerase chain reaction (PCR) test panels, capable of detecting eight of the most clinically relevant alleles of the CYP2D6 gene (*2, *3, *4, *6, *9, *10, 17, *41) and the three most common nonfunctional alleles of CYP2C19 (*2, *3, *4). The assays have been thoroughly validated using a large collection of reference samples, by parallel testing and by DNA sequencing. The reanalysis of reference samples provided the calculation of the frequency of the CYP2D6*4K allele in a population, not previously reported. Furthermore, original test results from CYP2D6*41, generated based on the presence of the 2850T and the lack of the −1584G single-nucleotide polymorphism (SNP), were compared with genotyping based on the current acknowledged founder SNP 2988G of this allele. These results indicate that up to 17.7% of the patients originally tested as carriers of the CYP2D6*41 allele may have had an incorrect phenotypic result assigned. The two 5′ nuclease real-time PCR test panels have subsequently been optimized for use in the clinical laboratory, using a standard real-time PCR instrument and software. Keywords: genotyping, 5′ nuclease assay, drug metabolization, CYP2C19, CYP2D6, pharmacogenetics